Utilization of TikTok in the Cooperative Learning Model on the Material of Creative Dance Characteristics in Class XI-1 of SMA Negeri 1 Tapa - Siti Aliyah Hasan; Mimy Astuty Pulukadang; Nurlia Djafar; Rahmawati Ohi; Riana Diah Sitharesmi (International Journal of Science and Environment (IJSE), 2026)
This study aims to describe the use of the TikTok application in a cooperative learning model on the characteristics of creative dance in class XI-1 of SMA Negeri 1 Tapa. This study uses a qualitative approach with descriptive methods. The research subjects consisted of Arts and Culture teachers and class XI-1 students of SMA Negeri 1 Tapa. Data collection techniques were carried out through observation, interviews, and documentation. Data analysis was carried out through the stages of data reduction, data presentation, and drawing conclusions. The research results show that the use of the TikTok application in a cooperative learning model has a positive impact on the learning process of students. The use of TikTok videos helps students understand the elements of dance, such as space, time, and energy in a more concrete and engaging manner. Furthermore, the implementation of the cooperative learning model can increase student activity, creativity, cooperation, and self-confidence during the learning process. Students appear more enthusiastic in discussions, dance practices, choreography preparation, and the process of documenting creative dance videos using the TikTok application. Learning that previously tended to be teacher-centered has changed to a more student-centered learning. Based on the results of the study, it can be concluded that the use of the TikTok application in the cooperative learning model is effective in learning the characteristics of creative dance because it is able to create a more active, creative, interactive, and enjoyable learning atmosphere and helps improve students' understanding and skills in learning Arts and Culture.